Impact of digital competencies and assistive technologies on learning outcomes for students with learning disabilities in Kingdom of Saudi Arabia: a systematic review - Hamid, Mohamed S.; Abo Hamza, Eid G.; Bedewy, Dalia; Elsiddig, Fatma Mohamed Elkhier; AlShammari, Saud Ayed; Bakhiet, Salaheldin Farah; Mohamed, Nagwa Ibrahim A. (Frontiers in Education, 2025)
BackgroundAssistive technology (AT) offers a vital role in providing a learning environment for disabled students. This paper investigates the role of AT and digital skills in enhancing learning outcomes for Kingdom of Saudi Arabia (KSA) students having Learning Disabilities (LD).ObjectivesThis review aims to explore the extent of technological applications to support students face LD. This review identifies the core skills that require further enrichment and the technological tools used for skill development, the impact of technological tools on the performance of students with LD, and investigate a variety of research on technological amelioration to assist KSA students with LD. The study also covers various research domains where further exploration is vital.MethodsThe review encompasses a detailed investigation of 35 research articles in the specific range of 2014–2025. In the study, 24 papers (69%) were targeted at primary and middle schools. The remaining 11 (31%) studies involved other participants such as University or special education. The review process encompasses 09 databases and follows a systematic and widely recognized approach of PRISMA 20 guidelines.ResultsThe review revealed that past studies focused on multiple baseline designs focusing primarily on elementary school students and a few other educational settings such as special education and university. The review also highlights key skills where research elevation is of utmost value, and fruitful outcomes can be attained by applying technological tools to support these skills. Further, the review outcome demonstrates that technological tool applications have a positive impact on students’ performance.ConclusionThe review unveiled that Dyslexia disability is the most common in students with LD, constituting 12 papers (34%), followed by Dyscalculia and Attention-Deficit/Hyperactivity Disorder (ADHD). The review outcome recommends various elucidations, including expanding teacher training programs, addressing infrastructural gaps, and conducting more localized studies in Kingdom of Saudi Arabia (KSA).